Laser lithotripsy is safe and effective treatment for ureteral calculi - Shah, Rajiv; KC, Sudeep Raj; Timilsina, Bhusan Raj (Journal of Chitwan Medical College, 2018)
This is hospital based prospective study done in the urology unit of Chitwan Medical College, Bharatpur. All patients who were subjected for ureteroscopy and lithotripsy were included in the study between January 01, 2018 to May 31, 2018. Hundred patients with 116 stones were treated with the Holmium laser Versa Pulse P20 Laser Lithotripter. Overall stone clearance rate was 97%. The more the stone burden less was the stone clearance rate. The major complications were perforation and postoperative fever which occurred in 11% of each case. This procedure is a safe and effective treatment for ureteric calculi and is associated with a low complication rate and a high clearance rate. Laser lithotripsy is the optimum ureteroscopic method of treating ureteric.